2008
DOI: 10.1590/s1677-54492008000300005
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da maturação das fístulas arteriovenosas para hemodiálise pelo eco-Doppler colorido

Abstract: ResumoContexto: Quando se confecciona uma fístula arteriovenosa para hemodiálise (FAVH) autógena, é necessário que se aguarde a dilatação da veia em questão e o desenvolvimento de volume de fluxo mínimo, fenômeno chamado de maturação. Ainda hoje se discute qual o tempo necessário para ocorrer essa maturação.Objetivo: Avaliar a maturação de FAVH utilizando-se critérios ecográficos. MHz para a avaliação no pré-operatório e nos 7º, 14º, 21º e 28º dias de pós-operatório. Os critérios para a maturação após a cirurg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 32 publications
1
12
0
4
Order By: Relevance
“…Our study found data similar to Toregeani et al They evaluated the arteriovenous fistula maturation process by serial DUS monitoring as for the progression of the diameter of the draining vein and flow, especially for fistulas on the wrist 12 . Data from the NKF-K/DOQI 13 , when compared to ours, differ in cutoff points, since the rule of three "6" could hardly be applied to our reality, especially when we would have to consider veins with a minimum of 0.6cm in diameter to achieve the optimum condition of maturation of said vein.…”
Section: Discussion Discussion Discussion Discussion Discussionsupporting
confidence: 87%
“…Our study found data similar to Toregeani et al They evaluated the arteriovenous fistula maturation process by serial DUS monitoring as for the progression of the diameter of the draining vein and flow, especially for fistulas on the wrist 12 . Data from the NKF-K/DOQI 13 , when compared to ours, differ in cutoff points, since the rule of three "6" could hardly be applied to our reality, especially when we would have to consider veins with a minimum of 0.6cm in diameter to achieve the optimum condition of maturation of said vein.…”
Section: Discussion Discussion Discussion Discussion Discussionsupporting
confidence: 87%
“…A skilled and under-qualified team can determine if a fistula has matured. 19 No puncture was performed in any of the participants during the maturation period.…”
Section: Resultsmentioning
confidence: 99%
“…Com esta, é possível acompanhar o aumento tanto no diâmetro da veia como no fluxo, orientando o melhor momento para considerar as FAV maturadas e consequente liberação do uso do acesso para hemodiálise (Figura 3). Toregeani et al 9 referem, como critério de maturação, o diâmetro venoso maior que 4 mm e fluxo maior que 400 mL/ minutos. Segundo o mesmo autor, esses parâmetros são geralmente alcançados por volta da quarta semana para FAV distais e da segunda semana para as FAV proximais.…”
Section: Discussionunclassified